Application of the PBL Learning Model Using the TaRL Approach to Improve Critical Thinking Ability - Nisa, Ainun; Tajudin, Tajudin; Lefrida, Rita (CV. Rayyan Dwi Bharata, 2025)
This research aims to improve students' critical thinking skills in mathematics learning through a problem based learning model with the Teaching at the Right Level (TaRL) approach in class XI-3 students at SMAN Terpadu Madani Model in the even semester of the 2023/2024 academic year. Data collection methods use observation, cognitive tests, learning results documents. Having a final performance indicator of 78% (28 out of 36 students) got the complete category, with pre-cycle details of 33% (12 out of 36 students) getting the high category, in the first cycle 53% (19 out of 36 students) got the high category, In the second cycle, 78% (28 of 36 students) got the high category. So it can be concluded that the application of the Problem Based Learning model with the Teaching at the Right Level (TaRL) approach can improve students' critical thinking skills in mathematics lessons on polynomial material.